Abstract Contemporary Meaning of Sihah Sitta : تجرید صحاح ستہ کی عصری معنویت - Raza, Dr. Ahmad; Khan, Dr. Muhammad Karim; Sarwar, Dr. Muhammad (Al Khadim Research Journal of Islamic Culture and Civilization, 2023)
In today's era, work on abstraction of Sihah Sitta is necessary. Imams Sihah Sitta mention the same hadith multiple times under different chapters and issues, thus some hadiths are narrated eight or ten times or even more. Mentioning the traditions of the imams of hadith several times, although it is based on evidence and reasoning, it is also necessary for deriving problems, but this matter is a cause of difficulty for all students of hadith and sometimes researchers too. Therefore, abstraction is needed for sihah hadiths. The work that has been done before this with reference to abstracting Hadith Sihah Sitta is mostly in Arabic language, thus translation into Arabic as well as Urdu language is probably the first attempt. The number of hadiths and works included in Sihah Sitta is (471, 34), while after abstracting, this number is (9400). In this way, the collection of the decrees of the Prophet (peace and blessings of Allah be upon him) that has been conveyed to the Ummah by these most reliable muhaddiths should be easy to study. will go. The work of abstracting Sihah Sitta is for ordinary Muslims instead of scholars and researchers, because direct study of Sihah Sitta is more useful for scholars and researchers, however, this abstract is useful for scholars and researchers who lack time. Will be. This abstraction will be very useful for the teachers and students of hadith, because it will make the study of the hadiths of Sihah Sitta easier, because there is a thirst for knowledge in the prevalent study without understanding. Through this abstraction, it will be possible to study all the hadiths of Sihah Sitta in a short time. https://doi.org/10.5281/zenodo.10517372